Epidemiological profile of families according to insertion in the cash transfer program residing in the coastal cities in Northeastern Brazil (Research, Society and Development, 2021)
Objective: Investigating the epidemiological profile of families living in the coastal cities in northeastern Brazil, considering that the are registered in the Brazilian Cash Transfer Program (CTP). Methods: Cross-sectional study involving a probabilistic sample of 1,444 representative families of the region. A previously tested semi-structured questionnaire was used, containing questions about socioeconomic, demographic, anthropometric and health variables, and also the situation of food and nutritional security during the home visits. The family’s characteristics were simultaneously benefited and not benefited by the PSF that was compared. The results were expressed in proportions (%), with the respective prevalence ratio of 95% confidence interval as a measure of association, using Poisson regression analysis with robust adjustment of variance. Results: There were 729 (50.5%) families registered with the PSF. The variables that best discriminated the families benefited by the program were: homemaker's education